2012
DOI: 10.1038/srep00695
|View full text |Cite
|
Sign up to set email alerts
|

GTP binding and intramolecular regulation by the ROC domain of Death Associated Protein Kinase 1

Abstract: The ROCO proteins are a family of large, multidomain proteins characterised by the presence of a Ras of complex proteins (ROC) domain followed by a COR, or C-terminal of ROC, domain. It has previously been shown that the ROC domain of the human ROCO protein Leucine Rich Repeat Kinase 2 (LRRK2) controls its kinase activity. Here, the ability of the ROC domain of another human ROCO protein, Death Associated Protein Kinase 1 (DAPK1), to bind GTP and control its kinase activity has been evaluated. In contrast to L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…In addition, from this analysis it was shown that DAPK1, LRRK1, and LRRK2 can exist as homo- and heterodimers, conformations that may be critical for the functions of these proteins. [39,40] In contrast, the MASL1 interactome was fully detached from the other ROCO protein interactomes within this network, indicating a lack of common interactors between MASL1 and the other ROCO proteins on the basis of the existing literature.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, from this analysis it was shown that DAPK1, LRRK1, and LRRK2 can exist as homo- and heterodimers, conformations that may be critical for the functions of these proteins. [39,40] In contrast, the MASL1 interactome was fully detached from the other ROCO protein interactomes within this network, indicating a lack of common interactors between MASL1 and the other ROCO proteins on the basis of the existing literature.…”
Section: Resultsmentioning
confidence: 88%
“…MASL1 (unlike the other ROCO proteins) lacks an intrinsic kinase domain (Figure 1), therefore it can be hypothesized that its GTPase activity within the ROC domain may influence an extrinsic kinase domain. [39,49,50] The novel potential MASL1-interacting kinases identified in this screen may be downstream effectors of the switch-like GTPase activity of MASL1 and thus part of a reciprocal regulatory relationship.…”
Section: Discussionmentioning
confidence: 99%
“…DAPK1 binds GTP with a P‐loop motif within the ROC domain, mediating GTP hydrolysis (intrinsic GTPase activity) . A recent study showed that the GTP binding to ROC‐COR domain stabilized the dimeric form of DAPK1 over other possible oligomeric forms as well as regulating the kinase activity by promoting Ser308 phosphorylation in a complex intramolecular regulatory model . However, this model of regulation is not well‐established yet, therefore requires further investigation …”
Section: Dapk Family Structurementioning
confidence: 99%
“…Kinase assays were carried out as previously described Jebelli et al 2012). Protein concentrations used are indicated in figure legends.…”
Section: In Vitro Kinase Reactionsmentioning
confidence: 99%
“…Humans possess four ROCOs, namely leucine-rich repeat kinase 1 (LRRK1), leucine-rich repeat kinase 2 (LRRK2), death-associated protein kinase 1 (DAPK1), and malignant fibrous histiocytoma-amplified sequences with leucine-rich tandem repeats 1 (MASL1) (Lewis 2009;Civiero et al 2014). Human ROCOs are capable of binding guanine nucleotides via their ROC domain and nucleotide binding seems important for complex formation and kinase activity Jebelli et al 2012;Biosa et al 2013;Dihanich et al 2013), suggesting that this domain is a central hub in ROCO function. Although ROCO proteins have been formally described over 10 years ago, their cellular functions remain elusive as well as the mechanisms by which these proteins, together with other signaling molecules, regulate cellular processes.…”
mentioning
confidence: 99%